1991
DOI: 10.1063/1.461702
|View full text |Cite
|
Sign up to set email alerts
|

A study of the electronic structures of Pd−2 and Pd2 by photoelectron spectroscopy

Abstract: The ultraviolet negative ion photoelectron spectrum of Pd−2 is presented for electron binding energies up to 3.35 eV. The anion is prepared by sputtering in a flowing afterglow ion source. Multiple low-lying electronic states of Pd2, all unidentified previously, are observed with resolved vibrational structure. The spectrum shows two strong electronic bands, each with similar vibrational progressions. Franck–Condon analyses are carried out on the two transitions and molecular constants are extracted for the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 30 publications
7
29
1
Order By: Relevance
“…On the other hand, Watari and Ohnishi (1998) found that the CO is more stable than the Ih at N = 13 by density-functional calculations. Moseler et al (2001) were able to compare their results about vertical electron detachment energies for anionic clusters with the experimental data (Ervin et al, 1988;Ganteför and Eberhardt, 1996;Ho et al, 1991) obtaining a good agreement. At larger sizes, ab initio results are few, being restricted to the comparison of a small set of selected structures at some special sizes.…”
Section: Noble and Quasi-noble Metal Clustersmentioning
confidence: 58%
“…On the other hand, Watari and Ohnishi (1998) found that the CO is more stable than the Ih at N = 13 by density-functional calculations. Moseler et al (2001) were able to compare their results about vertical electron detachment energies for anionic clusters with the experimental data (Ervin et al, 1988;Ganteför and Eberhardt, 1996;Ho et al, 1991) obtaining a good agreement. At larger sizes, ab initio results are few, being restricted to the comparison of a small set of selected structures at some special sizes.…”
Section: Noble and Quasi-noble Metal Clustersmentioning
confidence: 58%
“…This means that a Pd 2 molecule coordinated between 4MP molecules binds approximately 3 times as strong as a Pd 2 dimer in vacuum, D e = 1.03 ± 0.16 eV [39]. This strong binding in gas phase (i.e., without considering the solvent) might possibly stabilize a vertical diffusion pathway for the Pd dimer, effectively promote permeation of Pd through the SAM, which is expected under non-electrochemical conditions.…”
Section: Horizontal Diffusion Across the Sammentioning
confidence: 95%
“…The calculated force constant indicates a typical covalent bond strength of the intermetallic bond in Pt 2 ͑C 6 H 6 ). 25,26 The ground state spectroscopic constants of Pt 2 ͑C 6 H 6 ) Ϫ and Pt 2 ͑C 6 H 6 ) are very similar to those of Pt 2 Ϫ and Pt 2 , respectively ͑Table I͒. The harmonic potential curves as deduced from the spectroscopic parameters are shown in Fig.…”
Section: Methodsmentioning
confidence: 88%
“…The hybridization of the d-orbitals of palladium with the frontier orbitals of benzene is evident from the enhanced photoelectron intensity above 2 eV where the transitions within the d-orbital region are predicted for palladium. 21,25 The photodetachment spectrum of Pd 2 Ϫ ͑Ref. 25͒ shows only a weak photoemission intensity in this binding energy region, which is explained by the small photoemission cross sections of the d-orbitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation